EKSISTENSI PONDOK PESANTREN DI TENGAH KEMODERNAN PESANTREN - Khairurrijal, Khairurrijal (El -Hekam, 2019)
The issue of this research was to understanding the tradition and education model stiil exists Musthafawiyah Islamic Boarding School since exists to this nowadays. The purpose of this study is to reveal why Musthafawiyah Islamic Boarding School stiil exists in the modernity Islamic Boarding School and consistenly in existenly tradition and education model. The research is using qualitative method whit type case study. The approach in the research is using historis-fhenomenologis. Techniques in collecting data is using observation dan interview. Sources of data in the research consist of the leader, teahers, students, and workersMusthafawiyah Islamic Boarding School.Data analysis techniques use data reduction, data presentation and conclusion.The results showed that existence Musthafawiyah Islamic Boarding School because five factor, (1) Musthafawiyah Islamic Boarding School management; desirability structural Musthafawiyah Islamic Boarding School for continue of tradition the construct Syekh Musthafa Husein, construct the thought of structural Musthafawiyah Islamic Boarding School to relevant education model of Musthafawiyah in midst modernisme education, (2) the traditional factor with to defend the yellow book as hand-grip the student at traditional Muslim school, (3) the economic factor;life expense and education which a relative cheap, (4) the sincerity teachers as dedication to Musthafawiyah Islamic Boarding School without view a give the retainer, and (5) the subservience and loyality the student at traditional Muslim school as implementation from a value atto teach.